Politik Hukum Hubungan Pusat dan Daerah dalam Penanggulangan Bencana - Murti Ayu Hapsari; Suswoto Suswoto; Nita Ariyani (Universitas Internasional Batam, 2021)
The 1945 Constitution of Republic of Indonesia states that it is mandatory for government to ensure all of citizen life and well-being in any conditions and to protect them. This mandate take its concrete form by constructing the relevant National Development Plan. The government responsibility in disaster management is in the hands of central and local government—it is supposedly in well-planned and integrated manner. However, in reality, there is still a lot of overlapping authority and bureaucracy from both the central and local or regional governments in disaster management. The harmonization is needed between the central and regional governments, with the basis of granting the widest possible autonomy within the framework of a unitary state. The purpose of this research is to identify the central and regional relationship arrangements in disaster management in the prevailing regulations and to identify steps that must be taken to realize the harmonization of regulation arrangement between the central government and the regions in disaster management. This research is a normative juridical research and uses a basic, systematic approach and the law synchronization approach. From this paper, it is found that the legal politics of central and regional relations in the planning document have been designed to always be synchronous and consistent and have a high level of harmonization, but in the implementation stage it still needs to be reviewed because there are still disharmony caused by the lack of involvement of local governments as partners and communication between the central government and the local government.